Teenage pregnancy and abortion: discourse, identity and power - Francois-Cull, Whitney Nikita (2022)
Drawing on a Feminist Critical Discourse Analysis approach, this study critically investigates teenage pregnancy Discourse. It takes a novel approach by examining the 1999 UK government-produced policy Discourse present within the highly influential Teenage Pregnancy Strategy (TPS), alongside an examination of discourse and identity produced in a series of in-depth, qualitative interviews with 9 women who terminated their pregnancies as teenagers between 2003 and 2015. In light of the negative view of teenage pregnancy within the UK, strategically presented within TPS, as well as the steady increase in incidences of abortion amongst teenagers since TPS’ dissemination, this thesis explores the impact of such a negative context on those who were pregnant as teenagers, which continues to affect their identity constructions well into adulthood, with a specific focus on those who chose to terminate their pregnancies.